The Impact of Instagram Social Media on Religious Behavior of Mosque Youth in Siumbut Baru Village - Hasan Sazali; Yusra Dewi Siregar; Ismayanti Afrina Putri (Master Program of Sociology, Universitas Malikussaleh,, 2020)
This study aims to find out (1)What content is contained in instagram secial media that affects the religious behavior of mosque adolescents in Siumbut Baru (2) Instagram Social Media which has an impact on the religious behavior of mosque adolescents (3)the effect of instagram on the mosque adolescent religious behavior. From the result of this study indicate that instagram social media gives influence to mosque youth through the use of features presented, so that with social media instagram teen mosque caneaffected by daily behavior that reflects islamic values through positive content that can mativate to carry out such worship to Allah SWT respect parents, is not excessive in worldly matters, cares for others. Then, invite others to promote social service activities based on information obtained in instagram religious accounts. Adolescent religious behavior can be explained by the use of content or features from instagram social media.